Complementary or alternative? The use of homeopathic products and antibiotics amongst pre-school children - Bishop Jackie; Northstone Kate; Hay Alastair D; Wye Lesley; Headley Judith; Thompson Elizabeth (BMC Family Practice, 2008)
Abstract Background Any intervention to reduce the inappropriate use of antibiotics for infections in children has the potential to reduce the selective pressure on antimicrobial resistance and minimise the medicalisation of self-limiting illness. Little is known about whether homeopathic products might be used by some families as an alternative to antibiotics or the characteristics of such families. We used the Avon Longitudinal Study of Parents and Children (ALSPAC) observational dataset to explore the hypothesis that the use of homeopathic products is associated with reduced antibiotic use in pre-school children and to identify characteristics of the families of pre-school children given homeopathic products. Methods Questionnaires data were completed by the parents of 9723 children while aged between 3–4.5 years in Bristol UK. Univariable and multivariable analyses were used to explore the relationships between antibiotic and homeopathic product use. Results Six percent of children had received one or more homeopathic products and 62% one or more antibiotics between the ages of 3 and 4.5 years. After adjustment for factors associated with antibiotic use, there was no association between homeopathic product and antibiotic use (adjusted OR = 1.02, 95% CI 0.84, 1.24). Factors independently associated with child homeopathic product use were: higher maternal education, maternal use of homeopathic products, maternal lack of confidence in doctors, mothers reporting that they were less likely to see doctor when the child was ill, children being given vitamins, watching less television and suffering from wheeze and food allergies. Conclusion In this observational study, the use of homeopathic products was not associated with decreased antibiotic consumption, suggesting the use of homeopathic product complements rather than competes with the use of antibiotics in pre-school children. The characteristics of mothers giving homeopathic products to their children are similar to those associated with adult self-administration.